Effect Of Catfish Addition On Organoleptic Properties, Nutritional Value, And Acceptability Of Molele Noodles In Pregnant Women - Ratna Yulianti; Made Darawati; Reni Sofiyatin; I Gde Narda Widiada (Jurnal Gizi Prima (Prime Nutrition Journal), 2025)
Background: Noodles are one of the most popular food products in Asia. In Indonesia, noodles are a very popular food for children and adults. Noodles have been used as an alternative food to replace rice. This is possible because of the practical nature of noodles, their good taste, relatively cheap price, and easy manufacturing process.Research Methods: This research uses an experimental design in the form of a one-factor Completely Randomized Design (CRD), namely the addition of catfish (t) consisting of 5 treatment levels. Organoleptic properties were assessed based on hedonic tests on 20 panelists of students majoring in nutrition. The best results will be given to consumer panelists, namely pregnant women in trimesters 2 and 3, a total of 30 people. Data analysis using One Way Anova at 95% confidence level or alpha 0.05.Research Result: ANOVA analysis showed a significant value (p<0.05) on color and overall. The treatment most favored by panelists was molele noodles, with the addition of catfish as much as 20% (t1). The nutrient content in 100 grams of molecule noodles consists of 196 kcal energy, 10% protein, 1% fat, 36% carbohydrate, 51.95% water content, and 0.58% ash content. The acceptance of molele noodles showed the results of 90% of the targets having acceptance in the good category and 10% in the poor category.Conclusion: The addition of catfish affects the organoleptic properties of color molele noodles. In 100 grams of molele noodles, there is energy of 196 kcal, 10% protein, 1% fat, 36% carbohydrates, 0.58% ash content, and 51.95% water content. Molele noodles have a percentage of good Acceptability≥ 90%, which means in the good category.